Sistem Informasi Manajemen Proyek Pengolahan Data Aset Laboratorium Komputer Berbasis Web - Taufik Qurrahman; Yahfizham Yahfizham (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Information systems technology is currently very necessary in the field of education, especially in utilizing computer laboratory assets. Unfortunately, computer laboratory asset data processing is still done manually using handwritten logbooks which have weaknesses in terms of time, efficiency and effectiveness in data processing. Therefore, a web-based information system project management system is a solution to overcome the problem of processing computer laboratory asset data. This system development approach uses the waterfall method which includes needs analysis, system design, implementation and testing of the system. The system design uses use case and activity diagrams which are the final product of this research. With this system, it is hoped that data processing can be accurate, handle data leaks and work processes will also be faster and more timely. System implementation. The system implementation is expected to improve the ability to process asset data in the computer laboratory.